Jewish hermeneutic method based on exegesis of Songs of Songs by Abraham Ibn Ezra and Luis de León - Clea Moreno-Szypowska , Jadwiga (Filozofia Chrześcijańska, 2021)
The aim of these article is to present the more important rules of Jewish exegesis developed mainly by Hillel on the example of a commentary on the Song of the Songs of Abraham Ibn Ezra and Luis de León. The text tries to show how traditional Jewishhermeneutics is used in the innovative commentaries of a scholar from Tudela from the XIth century and a theologian from Belmonte from the XVIth century and how the first infl uenced the second. Interpretative methods developed in the most important centers of Judaic thought of the beginning of our era have been used for centuries to explain biblical texts, especially such as Song of Songs, which is recognized by both Old Testament and New Testament commentators as one of the most diffi cult and most mystical Scriptures.